Dialog polsko-rosyjski w twórczości Natalii Gorbaniewskiej, czyli o tym jak „Pokochałam te wiersze obce…” - Jawdosiuk, Anna (Acta Polono-Ruthenica, 2011)
Natalia Gorbanievskaya is a perfect example of a person who for years have been conducting the Polish-Russian Dialogue, as a poet, journalist, translator, social activist, defender of human rights and above all as a Giedroyc, Milosz, Kuron, Pomianowski and Walentynowicz friend. Polish poetry, prose, journalism and people have awaken love for Polish culture in the poet. Among these people Jerzy Giedroyc plays the most important role. The editor of the Parisian Kultura and Gorbanievskaya were linked primarily with community of values, respect for human individuality, dissent, the ability to conduct discussions on the arguments. Publicist shared with Editor political views concerning the eastern Polish politics, the position of Ukraine after the collapse of the Soviet Union, state of the Baltic States and Belarus on the map of Europe after 1991. Poets cooperation with Kultura has resulted in editorial activity, translational and publi- shing in the pages of Nowaja Polsza. The main topic of Natalia Gorbanievskaya journalism is also Jerzy Pomianowskis monthly aimed at the Russian intelligentsia in order to work out mutual respect and understanding between Poles and Russians.